Respostas
respondido por:
14
0,25^x = 64
(1/4)^x = 2^6
2^(-2x) = 2^6
-2x = 6
x = -6/2 = -3
(1/4)^x = 2^6
2^(-2x) = 2^6
-2x = 6
x = -6/2 = -3
respondido por:
13
25:25------ 1 ------- 1
--------- = ------ = ------- = 2^-2
100:25----- 4 ------ 2^2
64/2
32/2
16/2
8/2
4/2
2/2
1
64 = 2^6
log64 na base 0,25
0,25^x = 64
2^-2x = 2^6
- 2x = 6
multiplique por (-1)
- 2x = 6 .(-1)
2x = - 6
x =
x = - 3
resposta: log 64 na base 0,25 = - 3
--------- = ------ = ------- = 2^-2
100:25----- 4 ------ 2^2
64/2
32/2
16/2
8/2
4/2
2/2
1
64 = 2^6
log64 na base 0,25
0,25^x = 64
2^-2x = 2^6
- 2x = 6
multiplique por (-1)
- 2x = 6 .(-1)
2x = - 6
x =
x = - 3
resposta: log 64 na base 0,25 = - 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás